Scouting Program Management for the Formation of Gudep Leadership Character 19789-19790 - Habib, Fachri; Nur, Agung Muhammad; Nurmaini, Ella; Br Lubis, Melati; Siregar, Ahmad Rinaldi; Budi, Budi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This abstract discusses the importance of structured and directed scouting program management in forming leadership character in Gudep 19789-19790. This research analyzes existing scouting programs, identifies factors that influence program effectiveness, and formulates strategies to create more optimal leadership programs. This research found that the scouting program has great potential in building leadership character, especially through practical experience, leadership training, and developing group life values. This research provides practical recommendations for the leaders of Gudep 19789-19790 in planning, implementing and evaluating effective leadership programs, so as to create a young generation who have a strong leadership spirit, integrity and responsibility.